Genetic Structure of the Norwegian Parastagonospora nodorum Population - Lin, Min; Ficke, Andrea; Cockram, James; Lillemo, Morten (Frontiers in Microbiology, 2020)
The necrotrophic fungal pathogen Parastagonospora nodorum causes Septoria nodorum blotch (SNB), which is one of the dominating leaf blotch diseases of wheat in Norway. A total of 165 P. nodorum isolates were collected from three wheat growing regions in Norway from 2015 to 2017. These isolates, as well as nine isolates from other countries, were analyzed for genetic variation using 20 simple sequence repeat (SSR) markers. Genetic analysis of the isolate collection indicated that the P. nodorum pathogen population infecting Norwegian spring and winter wheat underwent regular sexual reproduction and exhibited a high level of genetic diversity, with no genetic subdivisions between sampled locations, years or host cultivars. A high frequency of the presence of necrotrophic effector (NE) gene SnToxA was found in Norwegian P. nodorum isolates compared to other parts of Europe, and we hypothesize that the SnToxA gene is the major virulence factor among the three known P. nodorum NE genes (SnToxA, SnTox1 and SnTox3) in the Norwegian pathogen population. While the importance of SNB as declined in much of Europe, Norway has remained as a P. nodorum hotspot, likely due at least in part to local adaptation of the pathogen population to ToxA sensitive Norwegian spring wheat cultivars.